2024
DOI: 10.1001/jamainternmed.2024.1132
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Circumstances and Racial Disparities in Cognition Among Older Adults in the US

Zhuoer Lin,
Justin Ye,
Heather Allore
et al.

Abstract: ImportanceGiven the critical role of neurocognitive development in early life, understanding the association between early-life circumstances and racial disparities in cognition has important implications.ObjectiveTo assess whether racial differences in early-life circumstances are collectively and individually associated with racial disparities in late-life cognition among older adults in the US.Design, Setting, and ParticipantsThis cross-sectional study used comprehensive life history data from the Health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Our study underscores that the negative association between school segregation and cognitive outcomes is more pronounced for Black than White participants, consistent with previous reseearch. 9,21,25,46 Moreover, our findings suggest that SES may explain a significant portion of the association between school segregation and cognition. We observed an approximately 50% reduction in the association among Black individuals after accounting for SES, highlighting the role of SES as potential mediators linking school segregation and cognition.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Our study underscores that the negative association between school segregation and cognitive outcomes is more pronounced for Black than White participants, consistent with previous reseearch. 9,21,25,46 Moreover, our findings suggest that SES may explain a significant portion of the association between school segregation and cognition. We observed an approximately 50% reduction in the association among Black individuals after accounting for SES, highlighting the role of SES as potential mediators linking school segregation and cognition.…”
Section: Discussionmentioning
confidence: 52%
“…Our results align with existing literature highlighting the negative association between adverse earlylife educational experiences and cognition in later life. 9 Notably, an increasing number of studies have indicated that higher educational quality is linked to a reduced risk of dementia and improved cognitive outcomes in later life. 41 , 42 Our analysis, drawing from comprehensive national datasets, offers broader contextual insights into the relationship between school segregation and cognition, setting it apart from studies that have relied on self-reported 19 21 or regional-specific data, 19 , 22 and/or those that have not focused specifically on cognition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations